The Role of Financial Literacy And Financial Inclusion In Improving Msme Performance: A Case Study In Kota Pari Village - Sari, Maya Macia; Sari, Pipit Buana; Pohan, Syahrial Hasanuddin; Syahputri, Rindi (Journal of Community Research and Service, 2023)
Studying the effects of MSMEs' financial literacy and inclusion on their performance in Kota Pari Village, PantaiCermin District, SerdangBedagai Regency was the focus of this research. The research is aimed squarely at the SME sector. Financial literacy and financial inclusion, which have been shown to boost MSMEs' productivity, will be the focus of this research. This study employs a descriptive, quantitative method based on multiple linear regression analysis techniques to examine the data. Thirty micro, small, and medium-sized enterprise (MSME) players made up the research samples. It is hoped that the findings of this study would increase financial literacy and promote financial inclusion in Kota Pari Village, PantaiCermin District, SerdangBedagai Regency, so that micro, small, and medium-sized enterprises (MSMEs) in the area can maximize their performance. The study found that a positive and substantial influence of financial literacy and financial inclusion on the performance of MSMEs was present at a total percentage of 48.2%.